Exploring the Linkage between the Neighborhood Environment and Mental Health in Guangzhou, China - Yingzhi Qiu (International Journal of Environmental Research and Public Health, 2019)
The relationship between the neighborhood environment and mental health has been investigated mostly in developed countries. Yet few studies have systematically examined the impact of the neighborhood-level built-environment and social environment on mental health within different localities in the Chinese context. Based on a household survey and geographical data in Guangzhou, China, this study aimed to explore the linkage between the neighborhood environment and mental health, with a particular focus on aspects of the built-environment that are related to new urbanism or compact cities and contextual social capital, using three geographic delineations. Our findings indicated that built-environment indicators based on a road network buffer had a higher explanatory power towards residents’ mental health than did those based on a circular buffer. The analytical models demonstrated that neighborhood floor-area ratio, building density, and per capita green area were positively correlated with mental health. Neighborhood safety and contextual neighborhood interactions and reciprocity had positive associations with mental health. These findings provide policy makers and urban planners with valuable information on the role of the compact city strategy and the neighborhood social environment to improve the mental health of residents.